International spillovers, knowledge acquisition and transfer among Japanese firms in the United States - Shang, Qingyan; Poon, Jessie P. H. (Journal of Business Economics and Management, 2013)
In this paper, we investigate (i) the relationship between international spillovers and knowledge acquisition, and, (ii) intra-firm subsidiary-to-parent transfer of technology among Japanese firms in the United States. Using a survey of 185 firms, probit regressions reveal that R&D personnel and market power significantly influence the acquisition of knowledge associated with basic and applied science and product development. Tacit knowledge that resides in customers, and skilled personnel are effective sources for exploitation of international knowledge spillovers. Participation in seminars and conferences also enhances the acquisition of applied science. Firms that rely on codified sources are unlikely to acquire any knowledge. This research also confirms other authors’ findings that subsidiary autonomy facilitates knowledge acquisition. In addition, knowledge in product development is most likely to lead to vertical intra-firm transfers while applied scientific research only results in the transfer of R&D capability. Scientific team visits from the US to Japan support subsidiaries’ transfer of R&D capability but teams sent from Japan to the US adversely affect transfers. Overall, our results suggest international spillovers are predominantly associated with the acquisition of tacit knowledge, and intra-firm transfers are most effective in the context of knowledge acquired in applied research and product development.First published online: 12 Sep 2012